Whole model empirical validation on a full-scale building. Issue 4 (3rd July 2016) - Strachan, Paul; Svehla, Katalin; Heusler, Ingo; Kersken, Matthias
Abstract : This paper describes an empirical validation study undertaken on two identical full-size buildings within the scope of the IEA ECB Annex 58 project. Details of the experimental configuration and monitoring are included, together with results from measurements and from predictions made by 21 modelling teams using commercial and research simulation programmes. The two-month, side-by-side experiment was undertaken on buildings with high levels of thermal mass and in a period with high solar gains. The detailed specification and associated measurement data provide a useful empirical validation dataset for programme testing. Results from the modelling demonstrate good agreement between measured data and predictions for a number of programmes, in both absolute predictions of temperatures and heat inputs as well as dynamic response. On the other hand, a significant number of user input errors resulted in poor agreement for other programmes, especially in the blind validation phase of the modelling methodology.